2020
DOI: 10.2196/15219
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Lifestyle Intervention to Prevent Type 2 Diabetes Through Healthy Habits: Design and 6-Month Usage Results of Randomized Controlled Trial

Abstract: Background Type 2 diabetes can be prevented through lifestyle changes, but sustainable and scalable lifestyle interventions are still lacking. Habit-based approaches offer an opportunity to induce long-term behavior changes. Objective The purposes of this study were to describe an internet-based lifestyle intervention for people at risk for type 2 diabetes targeted to support formation of healthy habits and explore its user engagement during the first 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
(48 reference statements)
3
25
0
Order By: Relevance
“…Although most participants had their first log-in on weekdays and during the day, 45%-48% of the participants chose to commence the studies outside common office hours when face-to-face psychological support is usually not offered. The log-in times were similar in the 2 studies regarding time of day and day of the week and also similar to what has been reported in other studies [ 30 ]. It is known that the time of day and the day of week people prefer to answer surveys are related to sociodemographic and health characteristics [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although most participants had their first log-in on weekdays and during the day, 45%-48% of the participants chose to commence the studies outside common office hours when face-to-face psychological support is usually not offered. The log-in times were similar in the 2 studies regarding time of day and day of the week and also similar to what has been reported in other studies [ 30 ]. It is known that the time of day and the day of week people prefer to answer surveys are related to sociodemographic and health characteristics [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although most participants had their first log-in on weekdays and during the day, 45%-48% of the participants chose to commence the studies outside common office hours when face-to-face psychological support is usually not offered. The log-in times were similar in the 2 studies regarding time of day and day of the week and also similar to what has been reported in other studies [30]. It is known that the time of day and the day of week people prefer to answer surveys are related to sociodemographic and health characteristics [31].…”
Section: Principal Findingssupporting
confidence: 87%
“…As StopDia was a clinical trial, we could not collect any contact information from the respondents before they had signed an informed consent face-to-face with the study nurse. Of the eligible respondents, 48.52% (5882/12,123) were willing to participate in the StopDia study; however, only 3271 people attended the RCT baseline visit, of whom 11.07% (362/3271) were found to have previously undiagnosed T2D and were thus excluded from the StopDia RCT [ 52 ]. The number of randomized participants in the StopDia RCT was 2909, which is less than half of the number eligible and willing based on the screening site data.…”
Section: Discussionmentioning
confidence: 99%